SINERGI KELEMBAGAAN DALAM UPAYA OPTIMALISASI PENGELOLAAN JARINGAN IRIGASI DI KECAMATAN SEDAYU KABUPATEN BANTUL - , IM. DENY KRISNA AJI, Dr. Agr. Sri Peni Wastutiningsih. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The research was conducted in Sedayu sub-district Bantul regency. It aimed to investigate what institutions which are involved in managing irrigation and theirpolicy, synergy models,how institutional synergy process built, and what kind of institutional synergy which is established to optimize irrigation management. The research method was qualitative exploratively which was developed by descriptive analysis. Informants were collected by purposive method. The main informants wereP3A in Argosari, Argodadi, Argorejo, and Argomulyo village. The key informants were Water Resource Agency, Agriculture and Forest Agency, sub-district government, village government and GP3A. The additional informants were agricultural extension workers and related parties which were developed exploratively. The methods used for data analysis were data reduction, data presentation by narrative containing tables, matrix, charts, and pictures